Optimal therapeutic strategy for treating patients with hypertension and atherosclerosis: focus on olmesartan medoxomil - R. P. Mason (Кардиоваскулярная терапия и профилактика, 2012)
Cardiovascular (CV) disease is a major factor in mortality rates around the world and contributes to more than one-third of deaths in the US. The underlying cause of CV disease is atherosclerosis, a chronic inflammatory process that is clinically manifested as coronary artery disease, carotid artery disease, or peripheral artery disease. It has been predicted that atherosclerosis will be the primary cause of death in the world by 2020. Consequently, developing a treatment regimen that can slow or even reverse the atherosclerotic process is imperative. Atherogenesis is initiated by endothelial injury due to oxidative stress associated with CV risk factors including diabetes mellitus, hypertension, cigarette smoking, dyslipidemia, obesity, and metabolic syndrome. Since the renin– angiotensin–aldosterone system (RAAS) plays a key role in vascular inflammatory responses, hypertension treatment with RAAS-blocking agents (angiotensin-converting enzyme inhibitors [ACEIs] and angiotensin II receptor blockers [ARBs]) may slow inflammatory processes and disease progression. Reduced nitric oxide (NO) bioavailability has an important role in the process of endothelial dysfunction and hypertension. Therefore, agents that increase NO and decrease oxidative stress, such as ARBs and ACEIs, may interfere with atherosclerosis. Studies show that angiotensin II type 1 receptor antagonism with an ARB improves endothelial function and reduces atherogenesis. In patients with hypertension, the ARB olmesartan medoxomil provides effective blood pressure lowering, with inflammatory marker studies demonstrating significant RAAS suppression. Several prospective, randomized studies show vascular benefits with olmesartan medoxomil: reduced progression of coronary atherosclerosis in patients with stable angina pectoris (OLIVUS); decreased vascular inflammatory markers in patients with hypertension and micro- (pre-clinical) inflammation (EUTOPIA); improved common carotid intima-media thickness and plaque volume in patients with diagnosed atherosclerosis (MORE); and resistance vessel remodeling in patients with stage 1 hypertension (VIOS). Although CV outcomes were not assessed in these studies, the observed benefits in surrogate endpoints of disease suggest that RAAS suppression with olmesartan medoxomil may potentially have beneficial effects on CV outcomes in these patient populations.